Studying the Mechanical Properties of Denture Base Materials Fabricated from Polymer Composite Materials - Jawad Kadhim Oleiwi (Al-Khwarizmi College of Engineering – University of Baghdad, 2018)
In this research, the effect of adding two different types of reinforcing particles was investigated, which included: nano-zirconia (nano-ZrO2) particles and micro-lignin particles that were added with different volume fractions of 0.5%, 1%, 1.5% and 2% on the mechanical properties of polymer composite materials. They were prepared in this research, as a complete prosthesis and partial denture base materials was prepared, by using cold cure poly methyl methacrylate (PMMA) resin matrix. The composite specimens in this research consist of two groups according to the types of reinforced particles, were prepared by using casting methods, type (Hand Lay-Up) method. The first group consists of PMMA resin reinforced by (nano-ZrO2) particles, while the second group consists of PMMA resin reinforced by (micro-lignin) particles.